CONVERSION OF LAPAROSCOPIC CHOLECYSTECTOMY INTO OPEN CHOLECYSTECTOMY: AN EXPERIENCE IN 300 CASES - Rashid, Tariq; Naheed, Asma; Farooq, Umar; Iqbal, Muhammad; Barakat, Najeeb (Journal of Ayub Medical College Abbottabad, 2016)
Background: Laparoscopic cholecystectomy is getting popularity in developing countries especially in Pakistan. Conversion from laparoscopic to open cholecystectomy is also common. This study intends to evaluate the causes of conversion from laparoscopic cholecystectomy to open cholecystectomy and to establish the efficacy and safety of the procedure. Methods: This descriptive case series was conducted in the department of General Surgery at Social Security Teaching Hospital Islamabad from November 2012 to October 2015. Patients of more than 20 years of age presenting in OPD with symptomatic gallstones were included in the study. Patients with dilated CBD (>8 mm in diameter), jaundice, acute cholecystitis, mass at porta hepatis and positive hepatitis B or C virology were excluded. Results: A total of 300 patients were included in the study; 262 (87.33%) were females and 38 (12.67 %) were males. Twenty-one (7%) patients were converted to open cholecystectomy. Most common cause of conversion was dense adhesions followed by obscure anatomy at Calot's triangle. Other common causes were bleeding, bile leakage, visceral injuries and instrument failure. In the first 100 cases, 10% patients were converted to open cholecystectomy followed by 6% in the next 100 cases. Only 5% patients were converted to open cholecystectomy in the last 100 cases. Conclusion: Most common cause of conversion from laparoscopic cholecystectomy to open cholecystectomy was dense adhesions followed by obscure anatomy at Calot's triangle. Keywords: Laparoscopic Cholecystectomy, Complications, Laparoscopy, conversion.